Spinocan 27G with Trendelenburg 15º Position Post Induction Anesthesia Can Reduce the Incidence of Hypotension in Subarachnoid Block Anesthesia - Gunawan, Rhesna Indra; Susana, Sarka Ade; Sutejo, Sutejo (Jurnal Keperawatan, 2024)
The surgery requires anesthesia, one of which uses the subarachnoid block anesthesia technique. Hypotension is a complication of subarachnoid block anesthesia which ranks highest in 70,7% of 82 respondents in one study. The prevalence of hypotension was reported in the last five years with different result each year starting 32,69%-76,9%. Hypotension can lead to reduces conditions consciousness, pulmonary aspiration, hypoventilation, tissue hypoxia and even death. This study to determine the comparison of the use of spinocan size and post anesthesia induction position on the incidence of hypotension in patients with subarachnoid block at RSUD Bendan Kota Pekalongan. Analytical observation with cross sectional design. The research was conducted in February - March 2024 with samples were 148 respondents with sampling using consecutive sampling technique based on inclusion and exclusion criteria. Anesthesia used spinocan size 27G and 25G, blood pressure was measured by bedside monitor. Data were analyzed using the Mann Whitney statistical test. The result showed that 84/144 respondents (56.8%) experienced hypotension. Data normality test showed that the data not normally distributed. The result of statistic test were obtained with p value 0.028 in the supine and trendelenburg groups with spinocan 27G. The statistical test results were p value 0.010 in in the supine and trendelenburg 15º groups with spinocan 27G. Obtained statistical test results p value 0.000 between the spinocan 27G and spinocan 25G groups in the incidence of hypotension. The Conclusion of the study, the size of the spinocan 27G and trendelenburg 15º position group significantly reduced the incidence of hypotension compared to the spinocan 25G and supine position group.